Mapping irrigation potential from renewable groundwater in Africa – a quantitative hydrological approach - Altchenko, Yvan; Villholth, Karen G. (Copernicus GmbH, 2014)
Groundwater provides an important buffer to climate variability in Africa. Yet groundwater irrigation contributes only a relatively little share of cultivated land, approximately 1% (about 2 million hectares) as compared to 14% in Asia. While groundwater is over-exploited for irrigation in many parts in Asia, previous assessments indicate an under-utilized potential in parts of Africa. As opposed to previous country-based estimates, this paper derives a continent-wide, distributed (0.5° spatial resolution) map of groundwater irrigation potential, indicated in terms of fractions of cropland potentially irrigable with renewable groundwater. The method builds on an annual groundwater balance approach using 41 years of data, allocating only that fraction of groundwater recharge that is in excess after satisfying other human needs and environmental requirements, while disregarding any socio-economic and physical constraints in access to the resource. Due to high uncertainty of groundwater environmental needs, three scenarios, leaving 30, 50 and 70% of recharge for the environment, were implemented. Current dominating crops and cropping rotations and associated irrigation requirements in a zonal approach were applied in order to convert recharge excess to potential irrigated cropland. Results show an inhomogeneously distributed groundwater irrigation potential across the continent, even within individual countries, reflecting recharge patterns and presence or absence of cultivated cropland. Results further show that average annual groundwater available for irrigation ranges from 692 to 1644 km3 depending on scenario. The total area of cropland irrigable with groundwater ranges from 27.2 to 64.3 million ha, corresponding to 12.5 to 29.6% of the cropland over the continent. The map is a first assessment that needs to be complimented with assessment of other factors, e.g. hydrogeological conditions, groundwater accessibility, soils, and socio-economic factors as well as more local assessments.